The impact of artificial intelligence on consumer behavior: Insights and implications - Meddah, Nadia (International journal of economic perspectives, 2024)
This paper aims to study the impact of artificial intelligence on consumer behavior, the study of consumer purchasing behavior is of great importance to marketers because it provides more understanding of the consumer's expectations, Emphasis has been placed on studying the impact on consumer behavior based on the use of artificial intelligence, which aims to gather greater information on consumers' needs and preferences and to employ them in such a way as to drive consumer decision-making, the subject's literature was reviewed to explain this impact. This study found an understanding of how artificial intelligence influences consumer purchasing behavior as it is necessary to understand the important role that artificial intelligence can play at each of the five stages that a consumer goes through when making a purchase decision.